2014
DOI: 10.1103/physreve.90.042305
|View full text |Cite
|
Sign up to set email alerts
|

Local shear transformations in deformed and quiescent hard-sphere colloidal glasses

Abstract: We performed a series of deformation experiments on a monodisperse, hard-sphere colloidal glass while simultaneously following the 3D trajectories of roughly 50,000 individual particles with a confocal microscope. In each experiment, we deformed the glass in pure shear at a constant strain rate (1 − 5 × 10 −5 s −1 ) to maximum macroscopic strains (5 − 10%), then reversed the deformation at the same rate to return to zero macroscopic strain. We also measured 3D particle trajectories in an identically-prepared q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 31 publications
5
72
1
Order By: Relevance
“…Though the linear stressstrain region in Fig. 1 is typically considered reversible, recent measurements have identified irreversible events and anelasticity on the micro-scale in this 'elastic' region [6,7,9,16,[19][20][21]]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the linear stressstrain region in Fig. 1 is typically considered reversible, recent measurements have identified irreversible events and anelasticity on the micro-scale in this 'elastic' region [6,7,9,16,[19][20][21]]. …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that amorphous solids do not possess a truly elastic response regime [6,7,9,16,[19][20][21]. For example, both a sublinear increase of stress versus strain (left inset to Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it is much more difficult to identify the relevant defects that control the mechanical response in amorphous materials 1 . Disordered materials span a wide range of length scales from atomic systems, such as metallic glasses 2 and ceramics 3 , to colloidal suspensions 4,5 , and macroscopic particulate materials, such as foams [6][7][8][9] , emulsions 10 , and granular matter [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these plastic events has been identified as isolated Eshelby quadrupoles that organize the nonaffine displacement field around a localized shear transformation. Indeed, the quadrupolar character of the displacement field has been verified experimentally by means of shear-deformation experiments on a monodisperse hard-sphere colloidal glass using confocal microscopy [8].…”
Section: Introductionmentioning
confidence: 99%